Getting to Know about Readability Level - Dhion Meitreya Vidhiasi (Saintara: Jurnal Ilmiah Ilmu-Ilmu Maritim, 2021)
English is a language that is still difficult to "conquer", especially with its status as a foreign language. Not only is it difficult in terms of pronunciation, but also most Indonesians still have difficulty understanding the English translation text that has been translated into Indonesian. This study will explain the level of readability of a reading text. The level of readability greatly affects how a text can be understood by readers who come from the target language. There are 3 (three) readability levels: high, medium, and low readability. In addition, there are several things that affect the readability of a translated text, such as the use of new words, idioms, and taxa sentences. Translating a word or a reading text not only requires knowledge of translation techniques but also the translator's competence and understanding of the context of the text to be translated.